THERAPEUTIC BICHECTOMY WITH AESTHETIC RESULTS NARRATIVE LITERATURE REVIEW - Hosni Chehade Hage, Moamar; Pilon Muknickas, Daniella; Reda Ahmad Hayek, Ricardo; Ribeiro Marques, Brenda; Aparecida Carvalho de Araújo, Maria; Teruo Suguihara, Roberto (Health and Society, 2023)
Introduction The surgical removal, known as Bichectomy, of Bichat’s ball, an adipose structure surrounded by a fibrous capsule evident in the middle third of the face, bilaterally, and with an auxiliary function in chewing and sucking, has been constantly and increasingly performed in the offices of specialists in orofacial harmonization (HOF), since its indications refer to aesthetics and therapy to avoid benign lesions in the cheek mucosa. Objective The objective of this research is to guide dental surgeons, specifically HOF specialists on surgical techniques and aesthetic and therapeutic indications. Methodology A bibliographic survey was carried out in the Scielo, PubMed and LILACS databases with the following terms: “bichectomy” and “orofacial harmonization”, and by crossing the Boolean descriptors <and> and <or>, the relationship between between expressions. Results The findings in the literature accurately indicate the bichectomy surgery, but, above all, report the need for regional anatomical knowledge in order to avoid iatrogenic events and improve the patient’s quality of life.